Child Protection Legal Perspective on the Educational Phenomenon of Students Selling in Schools - Meiske Lasut; Romi Mesra (Departement of Mathematics Education, 2024)
The aim of this research is to reveal how the legal perspective of child protection on the educational phenomenon of students who sell in schools. This method of research is the study of literature which collects data based on various references that are relevant to the research problem. The method of collecting data through various relevant references both available on the Internet and that are obtained manually such as books, and so on. Research findings revealed that based on the results of the child protection law perspective on the educational phenomenon of student sales at school, it can be concluded that the phenomena of children selling while at school is not all that means is a case of child exploitation. Others are volunteers for various reasons, whether to study entrepreneurship, study on their own, sell hobbies, help the family economy, pay for school, because there are no parents, and other reasons that even stories like this are inspired by others and even supported also by schools, their school friends, their communities, and netizens